Clinical Spectrum of Herpes Simplex Keratitis in a Tertiary Eye Hospital, Nepal - Shrestha, Poonam; Paudel, Santosh (Journal of Karnali Academy of Health Sciences, 2023)
Background: Ocular manifestations of herpes simplex virus infection range from benign blepharitis, conjunctivitis, and epithelial keratitis to vision-threatening stromal keratitis and uveitis. This study aims to find out the demographic profile, clinical manifestations of herpes simplex virus keratitis and to assess associated visual impairment in Nepalese population.Methods: The retrospective study was conducted from January 2020 – February 2022. The medical records were reviewed where visual acuity at presentation and at one month follow-up, clinical details on examination and, diagnosis of the stage of disease were noted.Results: Of 112 herpes simplex keratitis patients, mean age was 47.19±19.14 years. Patients of herpes simplex keratiris presented with different types of clinical manifestations namely 25 (22.31%) cases were dendritic and 13 (11.6%) geographic ulcers, 38 (33.9%) cases presented with purely stromal lesions, 19 (16.9%) cases with epithelial plus stromal lesions, 11 (9.8%) cases with stromal plus endothelial lesions and six (5.3%) cases with endothelitis. At presentation, 33 (29.4) had visual acuity of 6/6–6/18, 50 (44.6%) had 6/18–6/60, 6 (5.3%) had 6/60–3/60 and 23 (20.5%) had